Cylindrical lithium-chlorine secondary battery and method for manufacturing the same
Patent Information
- Application Number
- CN202611078870.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明的目的在于克服现有技术中圆柱型锂-氯二次电池中,放电产物LiCl固-固界面电子传输阻力大导致充电动力学缓慢,以及厚电极构型下离子扩散路径长导致浓差极化和容量衰减的问题
1、本发明提供了一种圆柱型锂-氯二次电池,其正极包含由第一材料与第二材料复合而成的异质结构复合材料,所述第一材料为VS2或VSe2,第二材料为WC或TiC,二者质量比为1:1.5~1:3。通过上述特定材料组合与质量比范围的协同作用,在正极内部构建连续的异质界面网络,利用功函数差异形成的内建电场驱动电子泵效应,一方面促进放电产物LiCl与正极界面处的电荷转移,降低LiCl氧化分解反应的活化能垒以降低其氧化分解能垒,另一方面将电化学反应界面从局域点接触转变为均匀平面接触,显著改善界面电荷转移效率并降低界面电子传输阻抗,从而有效克服圆柱型电池中固-固界面电子传输障碍与厚电极体相传质受限的耦合问题,使电池的充电极化电压显著降低,扩散阻抗降低50%以上,循环50次后容量保持率达89%以上。
Smart Images

Figure CN122907701A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a cylindrical lithium-chlorine secondary battery and its preparation method. Background Technology
[0002] The lithium-chlorine (Li-Cl2) secondary battery uses thionyl chloride (SOCl2) as the electrolyte solvent. During discharge, lithium chloride is generated at the positive electrode, and during charging, LiCl is reversibly converted into chlorine gas. This system has outstanding advantages such as high theoretical energy density, high operating voltage, and good adaptability over a wide temperature range, and has important application prospects in fields such as military special power supplies, polar / deep-sea exploration equipment, and emergency energy storage.
[0003] In terms of battery configuration selection, cylindrical batteries are considered the preferred option for the practical application of Li-Cl2 rechargeable batteries due to their mature manufacturing process, good sealing, and ease of large-scale assembly. However, in cylindrical battery configurations, to obtain sufficient capacity, the positive electrode is usually thicker, which limits electrolyte wetting, results in a long diffusion path for ions along the electrode thickness, and severe concentration polarization, leading to capacity decay and shortened cycle life. Simultaneously, the discharge product LiCl is an insulating solid, forming a solid-solid interface with the positive electrode material, resulting in extremely high electron transport resistance. Furthermore, the kinetics of LiCl oxidation and decomposition during charging are very slow, manifesting as high polarization voltage, low coulombic efficiency, and poor rate performance.
[0004] Researchers have explored various cathode materials, such as porous carbon, metal-organic frameworks, and transition metal chalcogenides, primarily aiming to enhance the adsorption capacity or catalytic conversion activity of chlorine species. However, these cathode materials are mainly suitable for coin cells. Due to the thin electrode and low charge loading in coin cells, bulk mass transfer is not a significant issue. Applying coin cell cathode materials to cylindrical cells does not significantly improve electrochemical performance. Existing technologies lack effective solutions to the limitations on solid-solid interface electron transport and bulk mass transfer that arise when the cathode charge loading increases by tens of times in cylindrical cells.
[0005] Therefore, it is of great significance to develop cathode materials that can simultaneously overcome the electron transport barrier at the LiCl solid-solid interface and the mass transfer limitation of the thick electrode bulk phase in cylindrical battery configurations. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems in existing cylindrical lithium-chlorine secondary batteries, such as slow charging kinetics due to the large electron transport resistance at the solid-solid interface of the discharge product LiCl, and concentration polarization and capacity decay due to the long ion diffusion path in thick electrode configurations. This invention provides a cylindrical lithium-chlorine secondary battery and its preparation method, wherein the positive electrode active material comprises a heterostructure composite material composed of VS2 or VSe2 and WC or TiC in a mass ratio of 1:1.5 to 1:3. This material combination constructs a continuous heterostructure network within the positive electrode, utilizing the built-in electric field generated by the work function difference to drive the electron pump effect, reducing the LiCl decomposition energy barrier and shortening the effective ion transport distance. This results in a battery cycle life of ≥50 cycles at 0.5 A / g, significantly reduced polarization, and a diffusion impedance reduction of over 50%.
[0007] The first aspect of the present invention provides a cylindrical lithium-chlorine secondary battery, comprising a cylindrical battery casing, a lithium metal negative electrode disposed within the casing, a positive electrode disposed within the casing, and an electrolyte impregnating the positive electrode and a separator, wherein the positive electrode active material comprises a composite of a first material and a second material; The first material is VS2 or VSe2, and the second material is WC or TiC; The mass ratio of the first material to the second material is 1:1.5 to 1:3.
[0008] The first aspect of the present invention provides a cylindrical lithium-chlorine secondary battery, wherein the positive electrode active material is composed of a first material and a second material, the first material being VS2 or VSe2, and the second material being WC or TiC, with a mass ratio of 1:1.5 to 1:3. The synergistic effect of the aforementioned specific material combination and mass ratio range enables the construction of a continuous heterogeneous interface network within the cathode. The design principle lies in the work function difference between the first and second materials, creating a built-in electric field at the contact interface that points from the material with the high work function to the material with the low work function. This built-in electric field drives an electron pump effect, promoting charge transfer at the interface between the discharge product LiCl and the cathode, lowering the activation energy barrier of the LiCl oxidation decomposition reaction, and transforming the electrochemical reaction interface from localized point contact to uniform planar contact, significantly improving interface charge transfer efficiency and reducing interface electron transport impedance. This simultaneously overcomes the coupling problem of solid-solid interface electron transport barriers and limited mass transfer in thick electrode bulk phases in cylindrical batteries, resulting in a significant reduction in charging polarization voltage at a cutoff capacity of 0.5 A / g and 70 mAh, a reduction in diffusion impedance of over 50%, and a capacity retention rate of over 89% after 50 cycles.
[0009] Furthermore, the work function of the first material (such as VS2) is approximately 4.6 eV, while the work functions of the second material (such as WC or TiC) are 4.9 eV and 5.3 eV, respectively. This significant work function difference of 0.3 to 0.7 eV ensures the formation of a stable built-in potential difference at the interface between the first and second materials, thereby providing a continuous driving force for the electron pump effect described in this invention.
[0010] Furthermore, the cylindrical battery has a specification of 14250 or 18505. These specifications are standard cylindrical battery dimensions selected from existing mature industrial systems for lithium-thionyl chloride primary batteries. This allows for full utilization of existing production line equipment, reducing industrial implementation costs. Simultaneously, this size range provides ample space for a positive electrode with a thickness of 80–200 μm, ensuring that the battery capacity meets practical application requirements and improving the battery's volumetric energy density.
[0011] Furthermore, the thickness of the positive electrode is 80–200 μm; the loading of active material in the positive electrode is 0.2–0.5 g; and the amount of electrolyte used is 3–6 mL. A positive electrode thickness of 80–200 μm ensures sufficient loading of active material while controlling the ion diffusion path within an acceptable range, avoiding insufficient capacity due to excessive thickness or hindered mass transfer due to excessive thickness. An active material loading of 0.2–0.5 g combined with an electrolyte volume of 3–6 mL ensures sufficient electrolyte wetting of the positive electrode carbon pack while avoiding excessive electrolyte reduction in battery energy density, thereby achieving a balanced optimization of capacity and kinetics.
[0012] Furthermore, the mass ratio of the first material to the second material is 1:1.5 to 1:2. The mass ratio of the first material to the second material is a key factor affecting the electrochemical performance of the battery. Controlling the mass ratio of the first material to the second material within a reasonable range can both form a sufficient heterogeneous interface density to ensure the full utilization of the electron pump effect and avoid excessive dilution of the catalytic conversion sites of the first material due to an excessive proportion of the second material. This can more effectively ensure the low polarization and long cycle life of the battery.
[0013] Furthermore, the porosity of the positive electrode is 50%–80%, and the mass ratio of the electrolyte to the positive electrode active material is 8:1–30:1. Reasonable control of the porosity ensures sufficient wetting of the electrolyte and rapid ion transport along the thickness of the thick electrode. Too low a porosity inhibits electrolyte wetting and ion diffusion, while too high a porosity leads to discontinuities in the conductive network and obstructed electron transport. A reasonable mass ratio of electrolyte to active material ensures sufficient wetting of the positive electrode carbon pack while avoiding excessive electrolyte reduction that lowers the battery energy density, thereby achieving synergistic optimization of ion conduction efficiency and energy density.
[0014] Furthermore, the electrolyte uses thionyl chloride as a solvent and contains Lewis acid and fluorinated lithium salt additives; The Lewis acid is selected from at least one of AlCl3, AlBr3, and FeCl3, and the concentration of the Lewis acid is 2-5 mol / L; The fluorinated lithium salt additive is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide, and the additive accounts for 0.5 to 5 wt% of the total mass of the electrolyte.
[0015] A Lewis acid concentration of 2–5 mol / L can provide sufficient ionic conductivity and ensure Cl- – The charge transfer efficiency of Cl2 conversion is affected by concentration; too low a concentration results in insufficient ionic conductivity, while too high a concentration increases viscosity, which in turn inhibits ion diffusion. Fluorinated lithium salt additives (0.5–5 wt%) can generate a stable, LiF-rich SEI film in situ on the lithium metal anode surface, effectively inhibiting lithium dendrite growth. Too low an addition results in an incomplete SEI film, while too high an addition leads to an excessively thick SEI layer, which in turn increases Li... + Migration resistance; thus, it can simultaneously ensure the high ion conductivity of the electrolyte and the stability of the negative electrode interface, thereby improving the coulombic efficiency and cycle stability of the battery.
[0016] A second aspect of the present invention provides a method for preparing the above-mentioned cylindrical lithium-chlorine secondary battery, comprising the following steps: (a) The first material and the second material are mixed, a dispersant is added and the mixture is ball-milled. After ball milling, the mixture is filtered, washed and dried, and then annealed under an inert atmosphere to obtain a positive electrode active material; wherein the first material is VS2 or VSe2 and the second material is WC or TiC. (b) The positive electrode active material obtained in step (a) is mixed with a conductive agent and a binder, and then granulated and dried to obtain positive electrode particles; (c) Prepare the electrolyte; (d) Attach the lithium metal negative electrode to the inner wall of the cylindrical battery casing, mold the positive electrode particles obtained in step (b) into a carbon pack and insert it into the central current collector, wrap it with a separator and place it in the center of the casing, inject the electrolyte obtained in step (c), and seal it.
[0017] The second aspect of this invention provides a method for preparing the aforementioned cylindrical lithium-chlorine secondary battery. The method involves mixing a first material and a second material, ball milling and annealing to obtain a positive electrode active material, then mixing it with a conductive agent and a binder to granulate it into positive electrode particles, and finally assembling them into a cylindrical battery. The design principle of this method is as follows: the ball milling process enables uniform mixing and sufficient contact of the two materials at the microscale; the annealing process promotes atomic interdiffusion and lattice matching at the interface to form a heterogeneous interface with a stable built-in electric field; and the granulation process obtains positive electrode particles with a concentrated particle size distribution to ensure a complete carbon-coated structure and uniform porosity after molding. This allows for a uniform and tightly bonded heterogeneous interface distribution in the prepared positive electrode active material, fully leveraging the electron pump effect, and enabling the assembled cylindrical battery to possess low polarization, long cycle life, and excellent rate performance.
[0018] Furthermore, in step (a), the ball milling speed is 200-500 rpm and the duration is 2-10 hours; and / or, the annealing temperature is 400-600 ℃ and the duration is 1-5 hours.
[0019] A ball milling speed of 200–500 rpm and a duration of 2–10 hours ensures that the two materials are thoroughly and uniformly mixed without damaging the crystal structure. If the speed is too low or the duration is too short, the mixing will be uneven and the number of heterojunctions will be insufficient. If the speed is too high or the duration is too long, it may lead to lattice damage or amorphization. An annealing temperature of 400–600 ℃ and a duration of 1–5 hours can promote interdiffusion of interfacial atoms and lattice matching to form a stable heterojunction. If the temperature is too low, the interfacial bonding strength will be insufficient. If the temperature is too high, it may cause particle agglomeration or the formation of a second phase. In this way, positive electrode active materials with high heterojunction density and tight bonding can be stably prepared.
[0020] Furthermore, in step (b), the mass ratio of the positive electrode active material to the conductive agent and binder is 7:2:1 or 8:1:1; and / or, the granulation is extrusion-spheronization granulation to obtain positive electrode particles with a particle size of 180-380 μm.
[0021] The 7:2:1 ratio is suitable for conventional conductivity requirements, while the 8:1:1 ratio further reduces the amount of conductive agent and increases the proportion of active material based on the inherent conductivity of the heterostructure composite material of this invention. Both ratios are effective solutions. Extrusion-spheronization granulation yields positive electrode particles with a particle size of 180-380 μm. The concentrated particle size distribution ensures uniform pores inside the carbon pack after molding and sufficient electrolyte wetting. It also avoids excessively fine particles leading to overly dense packing and reduced porosity, or excessively coarse particles leading to discontinuous conductive networks and obstructed electron transport. Thus, it can balance the integrity of the electrode structure with the efficiency of ion / electron transport.
[0022] Further, in step (c), the electrolyte uses thionyl chloride as a solvent and contains AlCl3 at a concentration of 2–5 mol / L, and a fluorinated lithium salt additive accounting for 0.5–5 wt% of the total mass of the electrolyte. The fluorinated lithium salt additive is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide (C2F6LiNO4S2, LiTFSI) and lithium bis(fluorosulfonyl)imide (LiN(SO2F)2, LiFSI).
[0023] An AlCl3 concentration of 2–5 mol / L ensures sufficient ionic conductivity in the electrolyte. A fluorinated lithium salt additive of 0.5–5 wt% can generate a stable LiF-enriched SEI film in situ on the lithium metal anode surface. Both LiTFSI and LiFSI have high thermal and electrochemical stability and can maintain the integrity of the SEI film under a wide temperature range. Thus, while ensuring the high ionic conductivity of the electrolyte, the stability of the anode interface can be improved, further extending the cycle life of the battery.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a cylindrical lithium-chlorine secondary battery, the positive electrode of which comprises a heterostructure composite material composed of a first material and a second material, wherein the first material is VS2 or VSe2, and the second material is WC or TiC, with a mass ratio of 1:1.5 to 1:3. Through the synergistic effect of the above-mentioned specific material combination and mass ratio range, a continuous heterostructure interface network is constructed inside the positive electrode. The built-in electric field formed by the difference in work function drives the electron pump effect, which on the one hand promotes charge transfer at the interface between the discharge product LiCl and the positive electrode, reduces the activation energy barrier of the LiCl oxidation decomposition reaction, and thus lowers its oxidation decomposition energy barrier. On the other hand, it transforms the electrochemical reaction interface from local point contact to uniform planar contact, significantly improving the interface charge transfer efficiency and reducing the interface electron transport impedance. This effectively overcomes the coupling problem of solid-solid interface electron transport barrier and limited mass transfer in thick electrode bulk phase in cylindrical batteries, resulting in a significant reduction in the charging polarization voltage, a reduction in diffusion impedance of more than 50%, and a capacity retention rate of more than 89% after 50 cycles.
[0025] 2. This invention provides a method for preparing a cylindrical lithium-chlorine secondary battery. The method involves mixing a first material and a second material at a mass ratio of 1:1.5 to 1:3, followed by ball milling and annealing to obtain a heterogeneous composite material. This composite material is then mixed with a conductive agent and a binder and granulated to obtain positive electrode particles. Finally, the particles are assembled into a cylindrical battery. This method achieves uniform mixing and sufficient contact of the two materials at the microscale through ball milling. Annealing promotes atomic interdiffusion and lattice matching at the interface to form a heterogeneous interface with a stable built-in electric field. Granulation yields positive electrode particles with a concentrated particle size distribution to ensure uniform carbon coating porosity after molding, thereby fully utilizing the electron pump effect. Furthermore, the annealing temperature is only 400–600 °C, effectively avoiding particle agglomeration caused by high-temperature processing. This method is highly compatible with existing battery manufacturing lines and is easy to scale up for mass production. Attached Figure Description
[0026] Figure 1 Scanning electron microscope (SEM) image of the VS2 / WC heterostructure composite material prepared in Example 1 of the present invention.
[0027] Figure 2 The images show the physical photos of the 14250 cylindrical lithium-chlorine secondary battery in Example 1 (right) and the 18505 cylindrical lithium-chlorine secondary battery in Example 2 (left).
[0028] Figure 3 This is the charge / discharge curve of the 14250 cylindrical battery in Embodiment 1 of the present invention under the cutoff capacity of 70 mAh mode.
[0029] Figure 4 The image shows the relaxation time distribution (DRT) of the electrochemical impedance spectroscopy of the VS2 / WC heterostructure composite material prepared in Example 1 of this invention. Detailed Implementation
[0030] The present invention will now be described in further detail with reference to specific embodiments. However, this should not be construed as limiting the scope of the present invention to the following embodiments; all technologies implemented based on the content of the present invention fall within the scope of the present invention.
[0031] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more. The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. To facilitate understanding of the invention, certain technical and scientific terms are specifically defined below. Unless otherwise expressly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by one of ordinary skill in the art to which this invention pertains. In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this invention, but do not exclude other aspects. In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur. To better understand the technical solutions of the above embodiments, the following more detailed experimental examples are provided for further explanation. Those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of this disclosure. Where specific techniques or conditions are not specified in the examples, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0032] In a specific embodiment of the present invention, the central current collector is made of stainless steel or nickel rod, and the separator is made of glass fiber. The specific materials and specifications mentioned above can be conventionally selected by those skilled in the art based on the battery model (e.g., 14250 or 18505) and the carbon pack size; these will not be elaborated upon in detail in the embodiments of the present invention.
[0033] Example 1 VS2 powder (99.9% purity) and WC powder (99.9% purity) were mixed at a mass ratio of 1:2, with VS2 at 1.0 g and WC at 2.0 g, for a total of 3.0 g. The mixed powder was placed in the grinding jar of a planetary ball mill, and 15 mL of anhydrous ethanol was added as a dispersant. The ball mill was set to 400 rpm, rotating clockwise for 2 hours and counterclockwise for 2 hours. After ball milling, the slurry was removed, washed three times with deionized water and anhydrous ethanol respectively, filtered, and the solid powder was collected. The powder was placed in a vacuum drying oven and dried overnight at 100 °C. The dried powder was transferred to a tube furnace and heated to 500 °C at a heating rate of 5 °C / min under an Ar atmosphere, held at that temperature for 2 hours, and then allowed to cool naturally to room temperature. The annealed product was gently ground and dispersed in an agate mortar and passed through a 200-mesh sieve to obtain the VS2 / WC heterostructure composite material.
[0034] The obtained VS2 / WC heterostructure composite material was characterized by scanning electron microscopy (SEM), such as... Figure 1 As shown in the figure, the light-colored particles are VS2 and the dark-colored particles are WC. The two phases are evenly distributed and the interface is clear and continuous. No obvious agglomeration or independent phase separation regions were observed. Ball milling and annealing treatments achieved uniform composite of the two materials at the microscale, forming a continuous heterogeneous interface network.
[0035] The above-mentioned VS2 / WC heterostructure composite material was mixed with a conductive agent (acetylene black) and a binder (PTFE) at a mass ratio of 7:2:1. An appropriate amount of anhydrous ethanol was added to form a paste. Spherical particles were prepared by extrusion-spheronization granulation machine, and the particles with a particle size between 180 and 380 μm (average particle size of about 280 μm) were passed through 40-mesh and 80-mesh sieves. The particles were dried in a vacuum drying oven at 80℃ for 12 hours to obtain positive electrode particles.
[0036] Figure 2 The images show actual photos of the 14250 cylindrical lithium-chlorine secondary battery assembled in this embodiment (right side of the image) and the 18505 specification battery in Example 2 (left side of the image).
[0037] In an argon glove box (H2O < 0.01 ppm, O2 < 0.01 ppm), anhydrous AlCl3 was added to a concentration of 4 mol / L using 4 mL of SOCl2 as solvent, and the mixture was magnetically stirred until completely dissolved, yielding a pale yellow solution. Then, 2 wt% LiFSI and 2 wt% LiTFSI were added to the solution, and stirring was continued for 20 minutes to obtain a homogeneous and transparent electrolyte.
[0038] In a dry environment with a dew point below -40 °C, a lithium metal anode (approximately 13.5 mm wide and 0.45 mm thick) was pressed onto the bottom and side walls of the inner wall of a 14250 cylindrical stainless steel casing, and anode tabs were welded on. 0.3 g of the above cathode particles were taken and molded into a cylindrical carbon pack under a pressure of 40 MPa. The porosity of the carbon pack was determined using mercury porosimetry (AutoPore IV 9500) at a pressure range of 0.5–60000 pSi, yielding a total porosity of approximately 65%. The carbon pack was tightly wrapped with a 14 mm diameter glass fiber separator, and the separator-wrapped carbon pack was placed in the center of the casing, ensuring insulation from the casing and the lithium anode. Approximately 4 mL of the above electrolyte was injected using a syringe, and the mixture was allowed to stand for 10–30 minutes to fully impregnate it. The battery casing was then placed in a laser sealing machine and sealed under an inert atmosphere. After assembly, the battery was allowed to stand for 8 hours before electrochemical testing.
[0039] Figure 3 The first charge-discharge curve of the 14250 cylindrical battery in this embodiment is shown in the 70 mAh cutoff capacity mode. The charging plateau is about 3.82 V, the discharging plateau is about 3.60 V, and the polarization voltage is only 0.22 V. The curve is stable without drastic fluctuations.
[0040] Figure 4 The image shows the relaxation time distribution (DRT) spectrum of the battery in Example 1. Compared with the VS2 material reference battery composed only of acetylene black and PTFE binder, the characteristic peaks in the mid-frequency region of the battery of this invention are significantly shifted to shorter time intervals and the peak areas are reduced, indicating that the heterostructure composite material significantly reduces the interfacial charge transfer impedance.
[0041] Example 2 VSe2 powder (99.9% purity) and TiC powder (99.9% purity) were mixed at a mass ratio of 1:1.5, with 1.0 g of VSe2 and 1.5 g of TiC, for a total of 2.5 g. The mixed powder was placed in the grinding jar of a planetary ball mill, and 15 mL of anhydrous ethanol was added as a dispersant. The ball mill was set to 200 rpm, rotating clockwise for 3 hours and counterclockwise for 3 hours. After ball milling, the slurry was removed, washed three times with deionized water and anhydrous ethanol respectively, filtered, and the solid powder was collected. The powder was placed in a vacuum drying oven and dried overnight at 100 °C. The dried powder was transferred to a tube furnace and heated to 400 °C at a heating rate of 5 °C / min under an Ar atmosphere, held at that temperature for 3 hours, and then naturally cooled to room temperature. The annealed product was gently ground and dispersed in an agate mortar and passed through a 200-mesh sieve to obtain the VSe2 / TiC heterostructure composite material.
[0042] The above-mentioned VSe2 / TiC heterostructure composite material was mixed with a conductive agent (acetylene black) and a binder (PTFE) at a mass ratio of 7:2:1. An appropriate amount of anhydrous ethanol was added to form a paste. Spherical particles were prepared by extrusion-spheronization granulation machine, and the particles with a particle size between 180 and 380 μm (average particle size of about 280 μm) were passed through 40-mesh and 80-mesh sieves. The particles were dried in a vacuum drying oven at 80 °C for 12 hours to obtain positive electrode particles.
[0043] In an argon-filled glove box, anhydrous AlCl3 was added to a concentration of 5 mol / L using 6 mL of SOCl2 as solvent and stirred magnetically until completely dissolved, yielding a pale yellow solution. Then, 2 wt% LiFSI of the total electrolyte mass was added, and stirring was continued for 20 minutes to obtain a homogeneous and transparent electrolyte.
[0044] In a dry environment with a dew point below -40 °C, a lithium metal anode (approximately 18.0 mm wide and 0.45 mm thick) was pressed onto the bottom and side walls of an 18505 cylindrical stainless steel casing, and anode tabs were welded on. 0.5 g of the above cathode particles were taken and molded into a cylindrical carbon pack (approximately 200 μm thick) under a pressure of 40 MPa. The porosity of the carbon pack was determined to be approximately 62% using mercury intrusion porosimetry. The carbon pack was tightly wrapped with an 18 mm diameter glass fiber separator, and the separator-wrapped carbon pack was placed in the center of the casing, ensuring insulation from the casing and the lithium anode. Approximately 6 mL of the above electrolyte was injected using a syringe, and the mixture was allowed to stand for 10–30 minutes to fully impregnate it. The battery casing was placed in a laser sealing machine and sealed under an inert atmosphere. After assembly, the battery was allowed to stand for 8 hours before electrochemical testing.
[0045] Example 3 VS2 powder (99.9% purity) and TiC powder (99.9% purity) were mixed at a mass ratio of 1:3, with VS2 at 1.0 g and TiC at 3.0 g, for a total of 4.0 g. The mixed powder was placed in the grinding jar of a planetary ball mill, and 15 mL of anhydrous ethanol was added as a dispersant. The ball mill was set to 300 rpm, rotating clockwise for 5 hours and counterclockwise for 5 hours. After ball milling, the slurry was removed, washed three times with deionized water and anhydrous ethanol respectively, filtered, and the solid powder was collected. The powder was placed in a vacuum drying oven and dried overnight at 100°C. The dried powder was transferred to a tube furnace and heated to 500°C at a heating rate of 5°C / min under an Ar atmosphere, held at that temperature for 5 hours, and then allowed to cool naturally to room temperature. The annealed product was gently ground and dispersed in an agate mortar and passed through a 200-mesh sieve to obtain the VS2 / TiC heterostructure composite material.
[0046] The above-mentioned VS2 / TiC heterostructure composite material was mixed with a conductive agent (acetylene black) and a binder (PTFE) at a mass ratio of 8:1:1. An appropriate amount of anhydrous ethanol was added to form a paste. Spherical particles were prepared by extrusion-spheronization granulation machine, and the particles with a particle size between 180 and 380 μm (average particle size of about 280 μm) were passed through 40-mesh and 80-mesh sieves. The particles were dried in a vacuum drying oven at 80℃ for 12 hours to obtain positive electrode particles.
[0047] In an argon glove box, anhydrous AlCl3 was added to a concentration of 2 mol / L using 3 mL of SOCl2 as solvent and stirred magnetically until completely dissolved, yielding a pale yellow solution. Then, 2.5 wt% LiFSI and 2.5 wt% LiTFSI (total 5 wt%) were added, and stirring was continued for 20 minutes to obtain a homogeneous and transparent electrolyte.
[0048] In a dry environment with a dew point below -40 °C, a lithium metal anode (approximately 13.5 mm wide and 0.45 mm thick) was pressed onto the bottom and side walls of the inner wall of a 14250 cylindrical stainless steel casing, and anode tabs were welded on. 0.2 g of the above cathode particles were taken and molded into a cylindrical carbon pack (approximately 80 μm thick) under a pressure of 40 MPa. The porosity of the carbon pack was determined to be approximately 78% using mercury intrusion porosimetry. The carbon pack was tightly wrapped with a 14 mm diameter glass fiber separator, and the separator-wrapped carbon pack was placed in the center of the casing, ensuring insulation from the casing and the lithium anode. 4 mL of the above electrolyte was injected using a syringe, and the mixture was allowed to stand for 10–30 minutes to fully impregnate the electrolyte. The battery casing was then placed in a laser sealing machine and sealed under an inert atmosphere. After assembly, the battery was allowed to stand for 8 hours before electrochemical testing.
[0049] Example 4 VSe2 powder (99.9% purity) and WC powder (99.9% purity) were mixed at a mass ratio of 1:1.5, with 1.0 g of VSe2 and 1.5 g of WC, for a total of 2.5 g. The mixed powder was placed in the grinding jar of a planetary ball mill, and 15 mL of anhydrous ethanol was added as a dispersant. The ball mill was set to a speed of 500 rpm, rotating clockwise for 1.5 hours and counterclockwise for 1.5 hours. After ball milling, the slurry was removed, washed three times with deionized water and anhydrous ethanol respectively, filtered, and the solid powder was collected. The powder was placed in a vacuum drying oven and dried overnight at 100 °C. The dried powder was transferred to a tube furnace and heated to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The annealed product was gently ground and dispersed in an agate mortar and passed through a 200-mesh sieve to obtain the VSe2 / WC heterostructure composite material.
[0050] The above-mentioned VSe2 / WC heterostructure composite material was mixed with a conductive agent (acetylene black) and a binder (PTFE) at a mass ratio of 7:2:1. An appropriate amount of anhydrous ethanol was added to form a paste. Spherical particles were prepared by extrusion-spheronization granulation machine, and the particles with a particle size between 180 and 380 μm (average particle size of about 180 μm) were passed through 40-mesh and 80-mesh sieves. The particles were dried in a vacuum drying oven at 80 °C for 12 hours to obtain positive electrode particles.
[0051] In an argon-filled glove box, anhydrous AlCl3 was added to a concentration of 5 mol / L using 4 mL of SOCl2 as solvent and stirred magnetically until completely dissolved, yielding a pale yellow solution. Then, 0.5 wt% LiFSI was added, and stirring was continued for 20 minutes to obtain a homogeneous and transparent electrolyte.
[0052] In a dry environment with a dew point below -40 °C, a lithium metal anode (approximately 18.0 mm wide and 0.45 mm thick) was pressed onto the bottom and side walls of an 18505 cylindrical stainless steel casing, and anode tabs were welded on. 0.3 g of the above cathode particles were taken and molded into a cylindrical carbon pack (approximately 150 μm thick) under a pressure of 40 MPa. The porosity of the carbon pack was determined to be approximately 60% using mercury intrusion porosimetry. The carbon pack was tightly wrapped with an 18 mm diameter glass fiber separator, and the separator-wrapped carbon pack was placed in the center of the casing, ensuring insulation from the casing and the lithium anode. Approximately 4 mL of the above electrolyte was injected using a syringe, and the mixture was allowed to stand for 10–30 minutes to fully impregnate it. The battery casing was placed in a laser sealing machine and sealed under an inert atmosphere. After assembly, the battery was allowed to stand for 8 hours before electrochemical testing.
[0053] Example 5 VS2 powder (99.9% purity) and WC powder (99.9% purity) were mixed at a mass ratio of 1:3, with VS2 at 1.0 g and WC at 3.0 g, for a total of 4.0 g. The mixed powder was placed in the grinding jar of a planetary ball mill, and 15 mL of anhydrous ethanol was added as a dispersant. The ball mill was set to 400 rpm, rotating clockwise for 1 hour and counterclockwise for 1 hour. After ball milling, the slurry was removed, washed three times with deionized water and anhydrous ethanol respectively, filtered, and the solid powder was collected. The powder was placed in a vacuum drying oven and dried overnight at 100 °C. The dried powder was transferred to a tube furnace and heated to 500 °C at a heating rate of 5 °C / min under an Ar atmosphere, held at that temperature for 2 hours, and then allowed to cool naturally to room temperature. The annealed product was gently ground and dispersed in an agate mortar and passed through a 200-mesh sieve to obtain the VS2 / WC heterostructure composite material.
[0054] The above-mentioned VS2 / WC heterostructure composite material was mixed with a conductive agent (acetylene black) and a binder (PTFE) at a mass ratio of 8:1:1. An appropriate amount of anhydrous ethanol was added to form a paste. Spherical particles were prepared by extrusion-spheronization granulation machine. The particles were passed through 40-mesh and 80-mesh sieves, and the particle size was taken between 180 and 380 μm (average particle size of about 380 μm). The particles were dried in a vacuum drying oven at 80 °C for 12 hours to obtain positive electrode particles.
[0055] In an argon-filled glove box, anhydrous AlCl3 was added to a concentration of 2 mol / L using 3.5 mL of SOCl2 as solvent and stirred magnetically until completely dissolved, yielding a pale yellow solution. Then, 5 wt% LiTFSI of the total electrolyte mass was added, and stirring was continued for 20 minutes to obtain a homogeneous and transparent electrolyte.
[0056] In a dry environment with a dew point below -40 °C, a lithium metal anode (approximately 13.5 mm wide and 0.45 mm thick) was pressed onto the bottom and side walls of the inner wall of a 14250 cylindrical stainless steel casing, and anode tabs were welded on. 0.2 g of the above cathode particles were taken and molded into a cylindrical carbon pack (approximately 80 μm thick) under a pressure of 30 MPa. The porosity of the carbon pack was determined to be approximately 80% using mercury intrusion porosimetry. The carbon pack was tightly wrapped with a 14 mm diameter glass fiber separator, and the separator-wrapped carbon pack was placed in the center of the casing, ensuring insulation from the casing and the lithium anode. 6 mL of the above electrolyte was injected using a syringe, and the mixture was allowed to stand for 10–30 minutes to fully impregnate it. The battery casing was placed in a laser sealing machine and sealed under an inert atmosphere. After assembly, the battery was allowed to stand for 8 hours before electrochemical testing.
[0057] Example 6 VSe2 powder (99.9% purity) and TiC powder (99.9% purity) were mixed at a mass ratio of 1:1.5, with 1.0 g of VSe2 and 1.5 g of TiC, for a total of 2.5 g. The mixed powder was placed in the ball mill jar of a planetary ball mill, and 15 mL of anhydrous ethanol was added as a dispersant. The ball mill was set to 350 rpm, rotating clockwise for 3 hours and counterclockwise for 3 hours. After ball milling, the slurry was removed, washed three times with deionized water and anhydrous ethanol respectively, filtered, and the solid powder was collected. The powder was placed in a vacuum drying oven and dried overnight at 100 °C. The dried powder was transferred to a tube furnace and heated to 550 °C at a heating rate of 5 °C / min under an Ar atmosphere, held at that temperature for 3 hours, and then allowed to cool naturally to room temperature. The annealed product was gently ground and dispersed in an agate mortar and passed through a 200-mesh sieve to obtain the VSe2 / TiC heterostructure composite material.
[0058] The above-mentioned VSe2 / TiC heterostructure composite material was mixed with a conductive agent (acetylene black) and a binder (PTFE) at a mass ratio of 7:2:1. An appropriate amount of anhydrous ethanol was added to form a paste. Spherical particles were prepared by extrusion-spheronization granulation machine, and the particles with a particle size between 180 and 380 μm (average particle size of about 250 μm) were passed through 40-mesh and 80-mesh sieves. The particles were dried in a vacuum drying oven at 80 °C for 12 hours to obtain positive electrode particles.
[0059] In an argon glove box, using 5 mL of SOCl2 as solvent, anhydrous AlCl3 was added to a concentration of 3 mol / L, and the mixture was magnetically stirred until completely dissolved, yielding a pale yellow solution. Then, 1.5 wt% LiFSI and 1.5 wt% LiTFSI (totaling 3 wt%) were added, and the mixture was stirred for another 20 minutes to obtain a homogeneous and transparent electrolyte.
[0060] In a dry environment with a dew point below -40 °C, a lithium metal anode (approximately 18.0 mm wide and 0.45 mm thick) was pressed onto the bottom and side walls of an 18505 cylindrical stainless steel casing, and anode tabs were welded on. 0.4 g of the above cathode particles were taken and molded into a cylindrical carbon pack (approximately 150 μm thick) under a pressure of 50 MPa. The porosity of the carbon pack was determined to be approximately 55% using mercury intrusion porosimetry. The carbon pack was tightly wrapped with an 18 mm diameter glass fiber separator, and the separator-wrapped carbon pack was placed in the center of the casing, ensuring insulation from the casing and the lithium anode. Approximately 5 mL of the above electrolyte was injected using a syringe, and the mixture was allowed to stand for 10–30 minutes to fully impregnate it. The battery casing was placed in a laser sealing machine and sealed under an inert atmosphere. After assembly, the battery was allowed to stand for 8 hours before electrochemical testing.
[0061] Comparative Example 1 The difference from Example 1 is that the first material is MoSe2, the second material is TiN, and the mass ratio of MoSe2 to TiN is 1:2 (i.e., 1.0 g of MoSe2 and 2.0 g of TiN). The other material types, process parameters (ball milling speed 400 rpm, forward rotation for 2 hours and reverse rotation for 2 hours, annealing temperature 500 ℃ and holding for 2 hours) and assembly conditions are the same as in Example 1.
[0062] Comparative Example 2 The difference from Example 1 is that the mass ratio of the first material VS2 to the second material WC is adjusted from 1:2 to 1:1, that is, VS2 and WC are each 1.5 g (the total amount remains unchanged at 3.0 g). All other material types, process parameters and assembly conditions are the same as in Example 1.
[0063] Comparative Example 3 The difference from Example 1 is that the mass ratio of the first material VS2 to the second material WC is adjusted from 1:2 to 1:4, that is, VS2 is 0.6 g and WC is 2.4 g (the total amount remains unchanged at 3.0 g). All other material types, process parameters and assembly conditions are the same as in Example 1.
[0064] Comparative Example 4 The difference from Example 1 is that the first material is replaced by MoS2 instead of VS2, the second material is kept unchanged by WC, and the mass ratio of MoS2 to WC is 1:2 (i.e., 1.0 g of MoS2, 2.0 g of WC, and a total of 3.0 g). All other process parameters and assembly conditions are the same as in Example 1.
[0065] Comparative Example 5 The difference from Example 1 is that the second material is replaced by NbN instead of WC, the first material remains unchanged at VS2, and the mass ratio of VS2 to NbN is 1:2 (i.e., VS2 1.0 g, NbN 2.0 g, total 3.0 g). All other process parameters and assembly conditions are the same as in Example 1.
[0066] Test methods Constant current charge-discharge tests were conducted using the LAND CT3002A battery testing system. Test conditions: current density 0.5 A / g (based on the mass of the first material VS2 or VSe2 in the positive electrode active material), charging in cutoff capacity mode (70mAh), and discharge cutoff voltage 2.0 V. Specific capacity values are calculated based on the mass of the composite material.
[0067] Impedance measurements were performed using a Gamry electrochemical workstation, with a frequency range of 0.01 Hz to 100 kHz and an amplitude of 10 mV. The diffusion impedance reduction rate was calculated as a benchmark against a cylindrical cathode cell made entirely of carbon material without heterostructure composite materials. The cathode of this benchmark cell was obtained solely from granulation of acetylene black and PTFE binder at a mass ratio of 8:2, with all other assembly conditions identical to those in Example 1. The charge transfer resistance of each example and comparative example was obtained by fitting EIS spectra to equivalent circuits, and the diffusion impedance reduction rate was calculated based on the change in the Warburg impedance coefficient.
[0068] The rate performance of the battery in Example 4 was tested, with current densities of 0.5, 1, 2, 5 and 10 A / g, and the cutoff capacity was set to 700 mAh / g.
[0069] Low-temperature impedance testing was performed on the battery of Example 4 at -10 °C using a Gamry electrochemical workstation with a frequency range of 0.01 Hz to 100 kHz and an amplitude of 10 mV.
[0070] Performance data Table 1. Electrochemical performance test results of Examples 1-6 and Comparative Examples 1-5 "—" indicates that the test was not conducted or the data is not applicable. Comparative Examples 1-5 did not have their 50-cycle retention rate tested because their capacity had decayed below the cutoff condition before 50 cycles.
[0071] As shown in Table 1, the polarization voltages of Examples 1-6 of this invention are 0.17–0.27 V, significantly lower than the 0.32–0.41 V of Comparative Examples 1-5; the capacity retention rate after 35 cycles is 93%–100%, and after 50 cycles it is 89%–98%, both significantly higher than the retention rates of Comparative Examples 1-5 in shorter cycle counts; the diffusion impedance reduction rate is 48%–58%, significantly higher than the 18%–30% of Comparative Examples 1-5. This invention, through the synergistic effect of specific material combinations (VS2 / VSe2 and WC / TiC) and a mass ratio range (1:1.5–1:3), constructs a continuous heterogeneous interface network inside the positive electrode. Utilizing the built-in electric field generated by the work function difference to drive the electron pump effect, it promotes charge transfer at the interface between the discharge product LiCl and the positive electrode, lowers the activation energy barrier of the LiCl oxidation decomposition reaction, effectively reduces its oxidation decomposition energy barrier, and promotes the charging process of Cl... – The invention achieves reversible conversion to Cl2 and transforms the electrochemical reaction interface from localized point contact to uniform planar contact, significantly shortening the effective transport distance of ions in the solid phase. This effectively overcomes the coupling problem of solid-solid interface electron transport barriers and limited mass transfer in thick electrode bulk phases in cylindrical batteries. As a result, the battery achieves a cycle life of over 50 cycles at a current density of 0.5 A / g and a cutoff capacity of 70 mAh, with a significantly reduced charging polarization voltage and diffusion impedance reduced by over 50%. Even at a high current density of 5 A / g, it retains over 80% of its capacity. Furthermore, the preparation process is mild (annealing temperature 400–600 °C), effectively avoiding particle agglomeration caused by high-temperature processing. It is highly compatible with existing battery manufacturing lines, easy to scale up production, and suitable for military special power supplies, polar / deep-sea exploration equipment, and emergency energy storage.
[0072] It should be noted that, through research, the inventors of this application have discovered that if only the first material (such as VS2 or VSe2) is used as the positive electrode active material without combining it with the second material, the intrinsic electronic conductivity of a single transition metal chalcogenide is low, and the discharge product LiCl tends to be deposited unevenly in an island-like manner on its surface. This results in a limited solid-solid interface contact area, leading to a continuous accumulation of interfacial charge transfer impedance with each cycle, causing rapid capacity decay and making it difficult to achieve stable cycling. If only the second material (such as WC or TiC) is used as the positive electrode active material without combining it with the first material, the catalytic activity of the second material for the LiCl / Cl2 redox reaction is significantly insufficient, failing to effectively drive the reversible reaction. Consequently, the reversible discharge capacity of the battery is extremely low, making it almost impossible to operate normally. A single material cannot simultaneously meet the dual requirements of catalytic activity and efficient charge transfer for the positive electrode of a lithium-chlorine secondary battery. By combining specific materials in this invention, the synergistic complementary effect of the two materials in catalytic activity and conductivity / work function matching can be achieved, thus realizing the low polarization and long cycle performance described in this application.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A cylindrical lithium-chlorine secondary battery, comprising a cylindrical battery casing, a lithium metal negative electrode disposed within the casing, a positive electrode disposed within the casing, and an electrolyte impregnating the positive electrode and a separator, characterized in that, The positive electrode active material is composed of a first material and a second material; The first material is VS2 or VSe2, and the second material is WC or TiC; The mass ratio of the first material to the second material is 1:1.5 to 1:
3.
2. The cylindrical lithium-chlorine secondary battery according to claim 1, characterized in that, The cylindrical battery has specifications of 14250 or 18505.
3. The cylindrical lithium-chlorine secondary battery according to claim 1, characterized in that, The thickness of the positive electrode is 80–200 μm; the loading of active material in the positive electrode is 0.2–0.5 g; and the amount of electrolyte used is 3–6 mL.
4. The cylindrical lithium-chlorine secondary battery according to claim 1, characterized in that, The mass ratio of the first material to the second material is 1:1.5 to 1:
2.
5. The cylindrical lithium-chlorine secondary battery according to claim 1, characterized in that, The porosity of the positive electrode is 50% to 80%; and / or, the mass ratio of the electrolyte to the positive electrode active material is 8:1 to 30:
1.
6. The cylindrical lithium-chlorine secondary battery according to claim 1, characterized in that: The electrolyte uses thionyl chloride as a solvent and contains Lewis acid and fluorinated lithium salt additives; The Lewis acid is selected from at least one of AlCl3, AlBr3, and FeCl3, and the concentration of the Lewis acid is 2-5 mol / L; The fluorinated lithium salt additive is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide, and the additive accounts for 0.5 to 5 wt% of the total mass of the electrolyte.
7. A method for preparing a cylindrical lithium-chlorine secondary battery as described in any one of claims 1-6, characterized in that, Includes the following steps: (a) The first material and the second material are mixed, a dispersant is added and the mixture is ball-milled. After ball milling, the mixture is filtered, washed and dried, and then annealed under an inert atmosphere to obtain a positive electrode active material; wherein the first material is VS2 or VSe2 and the second material is WC or TiC. (b) The positive electrode active material obtained in step (a) is mixed with a conductive agent and a binder, and then granulated and dried to obtain positive electrode particles; (c) Prepare the electrolyte; (d) Attach the lithium metal negative electrode to the inner wall of the cylindrical battery casing, mold the positive electrode particles obtained in step (b) into a carbon pack and insert it into the central current collector, wrap it with a separator and place it in the center of the casing, inject the electrolyte obtained in step (c), and seal it.
8. The preparation method according to claim 7, characterized in that: In step (a), the ball milling speed is 200-500 rpm and the time is 2-10 hours; and / or, the annealing temperature is 400-600℃ and the time is 1-5 hours.
9. The preparation method according to claim 7, characterized in that: In step (b), the mass ratio of the positive electrode active material to the conductive agent and binder is 7:2:1 or 8:1:1; and / or, the granulation is extrusion-spheronization granulation to obtain positive electrode particles with a particle size of 180-380 μm.
10. The preparation method according to claim 7, characterized in that: In step (c), the electrolyte uses thionyl chloride as a solvent and contains AlCl3 at a concentration of 2-5 mol / L, as well as fluorinated lithium salt additives accounting for 0.5-5 wt% of the total mass of the electrolyte. The fluorinated lithium salt additives are selected from at least one of lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide.